Endosperm cell size reduction caused by osmotic adjustment during nighttime warming in rice - Hiroshi Wada (Nature Portfolio, 2021)
Abstract High night temperature (HNT) often reduces yield in field crops. In rice, HNT during the ripening stage diminishes endosperm cell size, resulting in a considerable reduction in final kernel weight; however, little is known about the underlying mechanisms at cell level. In this study, we performed picolitre pressure-probe-electrospray-ionization mass spectrometry to directly determine metabolites in growing inner endosperm cells of intact seeds produced under HNT conditions, combining with 13C feeding and water status measurements including in situ turgor assay. Microscopic observation in the inner zone suggested that approximately 24.2% of decrease in cell expansion rate occurred under HNT at early ripening stage, leading to a reduction in cell volume. It has been shown that HNT-treated plants were subjected to mild shoot water deficit at night and endosperm cell turgor was sustained by a decline in osmotic potential. Cell metabolomics also suggests that active solute accumulation was caused by a partial inhibition of wall and starch biosynthesis under HNT conditions. Because metabolites were detected in the single cells, it is concluded that a partial arrest of cell expansion observed in the inner endosperms was caused by osmotic adjustment at mild water deficit during HNT conditions.